Exploring constructions of female surgeons’ intersecting identities and their impacts: a qualitative interview study with clinicians and patients in Ireland and Scotland - Offiah, Gozie; Cable, Stuart; Schofield, Susie; Rees, Charlotte E. (Frontiers in Medicine, 2024)
Introduction While many studies have explored surgeons’ personal and professional identities separately, our study is the first to examine intersecting female surgical identities. We explore intersecting surgical identities constructed by self and others (colleagues and patients) within two healthcare systems and their perceived impacts answering the research question: How do female surgeons’ constructed identities intersect, and what influences do those intersections have on their surgical lives? Methods We employed qualitative methodology drawing on semi-structured biographical narrative interviews underpinned by social constructionism. We employed intersectionality theory as an analytical lens. We adopted maximum variation sampling to identify diverse participants, including 38 surgeons (29 female; 9 male), 9 non-surgical colleagues (8 female, 1 male), and 13 patients of female surgeons (7 female, 6 male). Our 29 female surgeons also included six who had transitioned out of surgery. We analyzed the dataset using a five-step Framework Analysis approach. We captured talk about identities, as well as identity talk (constructions of identity through participants’ talk). Findings Multiple intersecting personal (not just gender) and professional identities were constructed and reported to have multiple impacts on female surgeons’ lives (including their education, training, and success). We present intersecting identities and their impacts relating to gender through four primary intersections: (a) gender + ethnic identities; (b) gender + parenthood identities; (c) gender + age identities; and (d) gender + professional identities (namely carer, competent, mentor/mentee, role model and leader). Our findings particularly highlight the challenges experienced by female surgeons of color, who are mothers, who are younger and/or who are leaders, illustrating diversity in women’s experiences beyond that of gender alone. Finally, we found unexpected insights into male surgeons and fatherhood. Discussion Intersectionality theory offered a novel analytical lens to extend existing knowledge on female surgical identities. Further research is warranted exploring intersecting identities of female surgeons of color, younger female surgeons, and male surgeons who are fathers, as well as identities unexplored in this study (e.g., diverse sexualities). We need to raise awareness of intersecting identities and their impacts in surgery, as well as providing training, allyship, and policy revision that is sensitive to intersectionality.